Toxoplasmic encephalitis associated with meningitis in a heart transplant recipient. Issue 4 (5th June 2014) - Baliu, C.; Sanclemente, G.; Cardona, M.; Castel, M.A.; Perez‐Villa, F.; Moreno, A.; Cervera, C.
Abstract Toxoplasma gondii is an opportunistic pathogen that causes neurologic and extraneurologic manifestations in immunosuppressed patients. Encephalitis and intracranial mass lesions are easily recognized as typical manifestations of toxoplasmosis. However, meningitis caused by T. gondii is a rare condition with very few cases described in the literature. We present the case of a heart transplant recipient who developed toxoplasmic encephalitis associated with meningitis. After an extensive review of the medical literature, we found only 1 case of meningitis in solid organ transplant recipients and <25 cases in immunosuppressed patients, such as patients infected with human immunodeficiency virus or those with Hodgkin's disease. In this report, we consider toxoplasmosis in the differential diagnosis of meningitis in immunocompromised individuals.